(untitled) ("Journal "U". Economy. Management. Finance.", 2022)
The article reveals the concept of a dividend, determines the moment of active emergence of the practice of dividend payments in joint-stock companies. In the course of the analysis of the market of oil and gas companies, it was found that the leading positions in this area are occupied by Gazprom, Rosneft, Transneft, Gazprom Neft, LUKOIL, TNK-BP and Surgutneftegaz. one of the hallmarks of a successful business.